KESESUAIAN LAHAN TANAMAN KEDELAI ( Glycine max (L.) Merill ) DI LAHAN PASIR PANTAI PARANGTRITIS KECAMATAN KRETEK, KABUPATEN BANTUL - Sandri Agustri Sari (FP AGRO 16 UMY 012, 2016)
A research entitled â€œLand Suitability for Soybean Crop (Glycine max (L.) Merill) in Sandy Coastal Land of Parangtritis Kretek District, Bantul Regencyâ€ was conducted in the coastal region of Parangtritis from in December 2015 up to April 2016. This research was conducted using observation method through the collection of primary and secondary data. Primary were all the information of soil characteristics which determined I the laboratory, while secondary data were all supporting information obtained from local government agencies. The result showed that coastal land of Parangtritis had sandy texture, soil drainage is very rapid, low to moderate soil effective depth, salinity is low, cation exchangable capacity is low, moderate to high base saturation percentage. Based on the soil characteristics and supporting data, actually this coastal land has land suitability class for soybean is N2r-1, r-2 with drainage and texture as the limiting factors. Drainage can be improved through continuously application of organic matter and potentially land is included in the class N2r-2 with texture as the limiting factor. Key words : sandy land, lan suitability, limiting factors, organic matter application.